ANALISIS KEMAMPUAN MENULIS NARASI SISWA KELAS IV SDN 32 CAKRANEGARA - Nuramaylia; Muhammad Makki; Siti Rohana Hariana Intiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the learning of narrative writing skills. The type of research used in this research is quantitative descriptive research. This research was conducted in class IV of SDN 32 Cakranegara. The data collection method used is the test method. The data analysis method used is quantitative analysis. The subjects in the research were the class IV homeroom teacher and 20 class IV students. The results of research regarding the ability to write narratives show that the ability to write narratives of class IV students at SDN 32 Cakranegara has an average score of 75.45 (good category). Based on the results of the analysis of the ability to write narrative essays of class IV students at SDN Cakranegara from the assessment guidelines for writing narrative essays which consist of 8 aspects, namely plot, characters, setting, content, content organization, word choice or diction, narrative text structure, and spelling and punctuation. . The category of students' narrative essay writing results showed good criteria totaling 13 students, adequate criteria totaling 5 students, and inadequate criteria totaling 2 students. The conclusion from this research is that most of the fourth grade students at SDN 32 Cakranegara have the ability to write good narrative essays.